Surfactant-assisted (CTAB, PVA, PVP) thermal decomposition synthesis of strontium spinel ferrite nanocrystals for electrochemical sensing of cytostatic drug flutamide. (December 2022) - Kesavan, G.; Pichumani, M.; Chen, S.-M.; Ko, C.-S.
Abstract: Nanostructured metal oxide (NMO)-based nanocatalysts are highly preferred in electrochemical sensing and other scientific disciplines due to their excellent catalytic or electrocatalytic activities. However, designing a simple and cost-effective NMO facilitator for improved catalytic activity remains a great challenge. As a result, added progress in surface engineering especially in the synthesis and optimization of catalysts is highly preferred. The main objective of the present investigation is to develop a facile, cost-effective, and dynamic catalyst for electrochemical sensing. Strontium ferrite nanocrystals (SF) were prepared using various surfactants (cetyltrimethylammonium bromide (SF-CTAB), polyvinyl alcohol (SF-PVA), and polyvinylpyrrolidone (SF-PVP) via the thermal decomposition method (TDM) and their effects on structure, morphology, and electro-reduction of flutamide (FLT) were thoroughly investigated. The cetyltrimethylammonium bromide (SF-CTAB) aggravated catalyst exhibited a higher surface area (8.51 m 2 /g), further demonstrating the higher electrochemical performance toward FLT detection when compared to surfactant-free and other surfactant stabilized catalysts. Importantly, the SF-CTAB catalyst established virtuous parameters such as a broader linear range from 0.016 to 658.51 μM, lowest detection limit (0.007 μM) with the remarkable anti-interference ability. Furthermore, it is notable that the proposed electrode modifier was effectively applied for the determination of FLT in both organic and environmental samples suggesting as an favorable candidate for sensing applications. Graphical abstract: Formation of strontium ferrite nanocrystals by thermal decomposition method using various surfactants. Image 1 Highlights: Facile, and one-step thermal decomposition synthesis of strontium spinel ferrite (SrFe2 O4, SF) nanocrystals is reported. The influence of surfactants on structural, morphological, and electrochemical performance was investigated. Morphology, specific surface area, and electrochemical properties vary with the different types of surfactants. Synthesized SF nanocrystals reveal substantial electrochemical performance with a broader linear range (0.016–658.51 μM) toward FLT detection.